Redescription of the phytosaurs Paleorhinus ('Francosuchus') angustifrons and Ebrachosuchus neukami from Germany, with implications for Late Triassic biochronology. (14th January 2014) - Butler, Richard J.; Rauhut, Oliver W. M.; Stocker, Michelle R.; Bronowicz, Robert
Abstract: Phytosaurs are a diverse and morphologically distinctive clade of superficially crocodile-like archosauriforms that had a near global distribution during the Late Triassic. Because their remains are among the most abundant vertebrate remains recovered in many Upper Triassic terrestrial formations, phytosaurs are used extensively in long-range biochronological and biostratigraphic correlations. The biochronologically oldest and earliest branching known phytosaurs include an array of nominal species from the early Late Triassic of the United States, Germany, Poland, Morocco, and India that have been synonymized within the genus Paleorhinus, and subsequently used to define a global ' Paleorhinus biochron'. However, recent phylogenetic work suggested that the North American species previously referred to Paleorhinus are paraphyletic. Here, we reassess the systematics and anatomy of putative specimens of Paleorhinus from southern Germany. Two well-preserved basal phytosaur skulls from the Blasensandstein (Carnian) of Bavaria form the holotypes of Francosuchus angustifrons and Ebrachosuchus neukami, both of which were synonymized with Paleorhinus by previous workers. We demonstrate that Francosuchus angustifrons shares unique synapomorphies with specimens referred to Paleorhinus bransoni from the Late Triassic of Texas, and thus refer the species to Paleorhinus . By contrast, the longirostrine Ebrachosuchus is highly distinctive in morphology, and our new cladistic analysis of Phytosauria demonstrates that it represents a valid taxon that is more closely related to Phytosauridae than to Paleorhinus . We provide the first autapomorphy-based support for a monophyletic but restricted Paleorhinus (supported by a nodal row on the jugal, and low paired ridges on the squamosal) and confirm that previous broader conceptions of Paleorhinus are likely to be paraphyletic. © 2013 The Linnean Society of London